Modern Literature of the Gulf - Michalak-Pikulska, Barbara; Michalak-Pikulska, Barbara (Peter Lang, 2016)
This book contains a selection of texts in Arabic Languages from the Gulf countries. The preceding study describes the beginnings of the literary movement in the Gulf region and presents the range of problems that appear in the regional literature. In this young and unknown literature reference is made to history as well as to social, political and cultural changes taking place in these countries. Without profound knowledge, a full understanding of the significance would be impossible. The selected works have intentionally not been translated to allow the reader an independent analysis. The author offers an outline of modern short story writing from the Gulf countries (Saudi Arabia, Oman, Bahrain, Qatar, Emirates and Kuwait) for all those interested in modern Arabic literature.